Geographical information system (GIS) application for planning and improvement of public water supply in Ota, Ogun State, Nigeria - GC Ufoegbune; PA Atanley; AO Eruola; AA Makinde; ZO Ojekunle (Journal of Applied Sciences and Environmental Management, 2017)
Geographical information system (GIS) technique is a useful tool for spatial analysis which has not been fully exploited in solving water issues in Ota hence the study. The study applied the tool of GIS in the planning and improvement of water supply system in Ota, Ogun state. This study harnessed the synergy of GIS and engineering designs to proffer an acceptable solution to the problems of water supply in the study area. Primary data generated on the field with GPS and spatial information were analysed with the aid of GIS to produce contour pattern and Digital Elevation Model (DEM) in form of maps. The study noted that the population would increase to almost double the present population by the year 2040 invariably resulting to an increase in water demand of the population beyond the capacity of the existing water supply facilities. Results also showed that water demand by the projected population by year 2040 will increase to 68.37 million litres per day while the existing facility has the capacity to produce about 9.2 million litres per day. Maps produced by the study included Contour, Digital Elevation and Existing and proposed pipeline network maps. These maps made available more information which can then be used for improving the water supply system. The study proffered a lasting solution through design of water scheme with capacity large enough to cater for water requirement of the population for the next twenty-five years irrespective of variation in water need of individual residents in the area with designs to improve distribution system through extension of pipelines and identification of various locations for service reservoirs.